Developing reading comprehension of hard hearing children using the I-hear program - Canon, Frances Kristine Villegas (2008)
The study aimed to develop the reading comprehension skills of the hard of hearing (HoH). Nine HoH students from 9-121 years old participated in the study. They were subjected to the I-HEAR program which integrated effective reading strategies, acoustic accomodations and spoken language techniques based on factors affecting the reading comprehension of HoH. It was found that HoH children possess the expected skills of their age in non-verbal knowledge but have poor reading comprehension skills. The I-HEAR program was able to develop the reading comprehension skills of the HoH with the use of Verbal Language Techniques, Acoustic accomodations, and reading strategies.
Thesis (M.Ed. Reading Education)--University of the Philippines, Diliman.
Keywords: Children with disabilities -- Education (Elementary) -- Philippines -- Manila Metropolitan Area; Hearing impaired -- Education (Elementary) -- Philippines -- Manila Metropolitan Area; Reading comprehension -- Philippines -- Manila Metropolitan Area